The Students’ Perception on Using Spotify Towards Their English Pronunciation - Joyce Purba; Laura Natalia; Lusiana Sapira (ENLIT, 2023)
Abstract: The purpose of this study is to investigate students' perceptions of the use of Spotify applications in improving their pronunciation ability. The participants of this study were 10 sixth-semester English education students at Palangka Raya University. The research design used in this study was qualitative description. Data were collected through a questionnaire and interview that assessed the effectiveness of using the Spotify application for students to improve their pronunciation ability. For the interview, there were 5 items and 10 questionnaire items. The results of this study revealed that using the Spotify application helped students improve their pronunciation, intonation, and vocabulary.